Affinity maturation of anti-(4-hydroxy-3-nitrophenyl)acetyl antibodies accompanies a modulation of antigen specificity. (February 2016) - Oda, Masayuki; Azuma, Takachika
Highlights: We analyze fine specificity, heterocliticity, of anti-NP antibodies. The antibodies preferentially bind to the phenolate form than to the phenolic form. The antibodies become more specific to NP during the process of affinity maturation. Abstract: Anti-(4-hydroxy-3-nitrophenyl)acetyl (NP) antibodies bearing λ 1 chains are known to possess fine specificity, referred to as heterocliticity, which causes these antibodies to bind to hapten analogues such as (4-hydroxy-3-iodo-5-nitrophenyl)acetyl (NIP) and (4-hydroxy-3, 5-dinitrophenyl)acetyl (NNP) with higher affinity than to the autologous hapten, NP. They also show preferential binding to the phenolate form of hapten than to the phenolic form. We address here the question of whether affinity maturation accompanies in the fine specificity of these antibodies by analyzing the interaction between NP1 -, NIP1 -, or NNP1 -hen egg lysozyme and anti-NP antibodies that possess different association constants to NP using a surface plasmon resonance biosensor. We measured interactions at various pH values and found that heterocliticity as well as preferential binding to the phenolate form of hapten were most prominent in a germline antibody having immature affinity and that fine specificity becomes less evident, i.e., anti-NP antibodies become more specific to the immunizing antigen, NP during the process of affinity maturation.